Corrosion, Tribology, and Tribocorrosion Research in Biomedical Implants: Progressive Trend in the Published Literature - Villanueva, J.; Trino, L. [UNESP]; Thomas, J.; Bijukumar, D.; Royhman, D.; Stack, M. M.; Mathew, M. T. (Springer Nature, 2017)
There has been significant progress in implant research during last the 10 years (2005–2015). The increase in the elderly population coupled with a lack of proper physical activity is a potential cause for the sudden increment in implant usage. Implant life and performance are influenced by several parameters; however, literature showed that corrosion, tribology, and tribocorrosion processes of implant materials are main concern and driving mechanisms in the degradation processes. There is currently a large need for research in this area. Furthermore, there has been no recent systematic literature review to analyze the progress of research and published work in this area. The objective of this work is to provide a trend in the published articles in the area of corrosion, tribology, and tribocorrosion during last century, with emphasis on the progress over the last 10 years. The paper also tries to report the current state-of-the-art research in the area of corrosion, tribology, and tribocorrosion research in bio-implants based on number of published articles. The reviews demonstrate that during the last 10 years, there has been significant progress in implant research, particularly in the tribocorrosion area, however, significantly lower than tribology and corrosion research.
Keywords: Biomedical Implant; Dental Health Care; Dental Implant; Final Table; Metal Hypersensitivity